Habitat Selectivity and Reliance on Live Corals for Indo-Pacific Hawkfishes (Family: Cirrhitidae) - Coker, D.; Hoey, A.; Wilson, S.; Depczynski, M.; Graham, N.; Hobbs, Jean-Paul; Holmes, T.; Pratchett, M. (2015)
Hawkfishes (family: Cirrhitidae) are small conspicuous reef predators that commonly perch on, or shelter within, the branches of coral colonies. This study examined habitat associations of hawkfishes, and explicitly tested whether hawkfishes associate with specific types of live coral. Live coral use and habitat selectivity of hawkfishes was explored at six locations from Chagos in the central Indian Ocean extending east to Fiji in the Pacific Ocean. A total of 529 hawkfishes from seven species were recorded across all locations with 63% of individuals observed perching on, or sheltering within, live coral colonies. Five species (all except Cirrhitus pinnulatus and Cirrhitichthys oxycephalus) associated with live coral habitats. Cirrhitichthys falco selected for species of Pocillopora while Paracirrhites arcatus and P. forsteri selected for both Pocillopora and Acropora, revealing that these habitats are used disproportionately more than expected based on the local cover of these coral genera. Habitat selection was consistent across geographic locations, and species of Pocillopora were the most frequently used and most consistently selected even though this coral genus never comprised more than 6% of the total coral cover at any of the locations. Across locations, Paracirrhites arcatus and P. forsteri were the most abundant species and variation in their abundance corresponded with local patterns of live coral cover and abundance of Pocilloporid corals, respectively. These findings demonstrate the link between small predatory fishes and live coral habitats adding to the growing body of literature highlighting that live corals (especially erect branching corals) are critically important for sustaining high abundance and diversity of fishes on coral reefs.